Effectiveness of paint psoralen and ultraviolet-A in alopecia areata - Our experience in the national skin center - Lucinda Siyun Tan; Melissa Mei Hsia Chan; Daryl Jian An Tan; Joyce Siong See Lee; Wei-Sheng Chong (Wolters Kluwer Medknow Publications, 2020)
Background: Alopecia areata (AA) is usually a benign cause of patchy hair loss that often resolves within a few weeks to months. Most treatment modalities are ineffective in the treatment of severe AA. The use of paint psoralen and ultraviolet-A (PUVA) in the treatment of patients with severe forms of AA has been reported in the literature. Aims and Objective: The aim of this study was to evaluate the effectiveness of paint PUVA therapy in the treatment of AA in Singapore. Materials and Methods: We performed a 10-year retrospective analysis of patients who underwent paint PUVA for AA. We evaluated patient demographics and treatment outcomes in the form of percentage change in baseline severity of alopecia tool score and final amount of hair regrowth and relapse rate. Results: Ten patients were included in this study. With paint PUVA therapy, significant hair regrowth was seen in six patients. Paint PUVA therapy in our study showed minimal side effects. Conclusion: PUVA gives fair response in AA in a reasonable time as per our center's experience in Singapore.